Tell the story of a virus. (February 2023) - Pearl, Monica B.
This article is part of the special Cultural Commons edition on It's a Sin . It argues that if It's a Sin is the queer Friends of the UK AIDS era, it loses its nerve: while it gets right the ways that queer kinship reinvented the conventional family during the AIDS crisis, it still makes the domestic sphere its ultimate thematic focus - and mothers the villains.